Pengaruh Latihan Multiball Terhadap Keterampilan Smash Forehand Tenis Meja Pada Club Pade Angen Mataram Tahun 2020 - Nurdin Nurdin; Aminullah Aminullah (Jurnal Ilmiah Mandala Education (JIME), 2020)
The focus of the problem in this study is that this research is motivated by the low accuracy of the forehand smash. Table tennis at Club Pade Angen Mataram in 2020. The research objectives to be achieved based on the predetermined problem formulation are as follows: To find out the effect of multiball training on the smash forehand table tennis skills at Club Pade Angen Mataram in 2020. The research design in use is an experimental research "One-Group Pretest-posttest Design". This experiment still has external variables that influence the formation of the dependent variable. So the experimental results which are the dependent variable (bound) are not merely influenced by the independent variable (free). Table Tennis Forehand Drive Accuracy Instrument To make it easier to understand below is a picture of a table marking sign of two targets on the right side of the testicle, namely the area of 30cm x 30cm, both of which are 60cm x 60cm. . Table Sampling technique using a population study of 12 players. Based on data analysis, getting the t-count obtained a value of 10.30 then the t-table with degrees of magnitude N - 1 = 11 at a significant level of 5% shows a number that is 1.796. This result means that the t-count> t-table, namely (3.995> 1.796) or in other words the t-count obtained is greater than the limit of the rejection of the null hypothesis (Ho), it is necessary that the t-value is equal to or greater than the t value. -table.